2014
DOI: 10.5489/cuaj.1884
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon-specific factors affecting treatment decisions among Canadian urologists in the management of pT1a renal tumours

Abstract: Introduction: The ubiquitous use of diagnostic imaging has resulted in an increased incidental detection of small renal masses (SRM). Patient-and tumour-related factors affect treatment decisions greatly; however, with multiple treatment options available, surgeonspecific characteristics and biases may also influence treatment recommendations. We determine the impact of surgeon-specific factors on treatment decisions in the management of SRM in Canada. Methods: An online survey study was conducted among Canadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The clinical implementation of pharmacogenetics in therapeutic approaches, aims to optimize specific drug regimens and drug dosage. This, may have a great advantage in, improving clinical outcomes and avoiding major clinical complication such as congestive heart failure, hepatic and renal disorders [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical implementation of pharmacogenetics in therapeutic approaches, aims to optimize specific drug regimens and drug dosage. This, may have a great advantage in, improving clinical outcomes and avoiding major clinical complication such as congestive heart failure, hepatic and renal disorders [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, respondents to recent physician surveys from Canada and the United States indicate that age and comorbid status influence their choice of surgery. 15,16 Also, previous population-based and large single centre studies reported that factors, such as younger age, male gender, and lower Charlson comorbidity score, were associated with increased use of partial nephrectomy. 22,27 We believe these data indicate that Canadian urologists working at academic centres are performing partial nephrectomies when technically feasible irrespective of most patient factors.…”
Section: Discussionmentioning
confidence: 99%
“…4,13,14 However, surveys done in Canada and the United States indicate considerable variation in patient management. 15,16 Furthermore, previous studies have indicated that partial nephrectomy may be underutilized. 5,17,18 Studies characterizing the management of stage 1 renal tumours in the United States indicate that although an increasing number of patients are receiving partial nephrectomy, most still receive radical nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our response rate parallels a previous Canadian survey on small renal masses, in which an 18% response rate was obtained. 10 Nevertheless, our results should be interpreted with caution and cannot be extrapolated to all Canadian practicing urologists. It may also be possible that a response bias toward those who had access to LTA in their institution is operational.…”
Section: Discussionmentioning
confidence: 84%